Non-Western and Western Theories of Peace - Steinmetz, Carl Hermann Dino (Advances in Social Sciences Research Journal, 2025)
This paper examines the divergent yet complementary approaches to peace in Western and non-Western theoretical traditions. Western theories—such as Democratic Peace Theory, Liberal Institutionalism, and Galtung’s Positive/Negative Peace—emphasize structural, state-centric mechanisms, including democratic governance, international organizations, and institutional justice. In contrast, non-Western philosophies—Ubuntu, Ahimsa, Confucian Harmony, Islamic Sulh, Indigenous Restorative Justice, and Buddhist Peace Theory—prioritize relational, spiritual, and communal dimensions of peace, focusing on interconnectedness, nonviolence, ethical harmony, and restorative dialogue. By juxtaposing these frameworks, the study reveals how Western models often address macro-level stability while non-Western traditions cultivate micro-level transformation. Ultimately, the paper argues for an integrated paradigm of peace that synthesizes institutional rigor with cultural and spiritual wisdom, offering a holistic response to global conflict.